1991
DOI: 10.1128/aac.35.3.410
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-(1-3)- and alpha-(1-6)-D-mannose-specific plant lectins are markedly inhibitory to human immunodeficiency virus and cytomegalovirus infections in vitro

Abstract: The alpha-(1-3)-D-mannose- and alpha-(1-6)-D-mannose-specific agglutinins (lectins) from Galanthus nivalis, Hippeastrum hybrid, Narcissus pseudonarcissus, and Listera ovata inhibited infection of MT-4 cells by human immunodeficiency virus types 1 and 2 (HIV-1 and HIV-2) and simian immunodeficiency virus at concentrations comparable to the concentrations at which dextran sulfate (molecular weight, 5,000 [DS-5000]) inhibits these viruses (50% effective concentration, 0.2 to 0.6 microgram/ml). Unlike DS-5000, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
166
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(171 citation statements)
references
References 28 publications
3
166
2
Order By: Relevance
“…Like Amaryllidaceae, onion and leek lectins, the orchid lectins were also shown to be very potent inhibitors of the infection of target cells by some human and animal retroviruses (Balzarini et al, 1991(Balzarini et al, , 1992. Using double-immunodiffusion assays it was shown that the orchid lectins isolated from L. ovata, E. helleborine and Cymbidium hybrid also react with antibodies raised against the snowdrop lectin and cross react with the G. nivalis lectin, indicating that these Orchidaceae lectins are serologically related to the snowdrop lectin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like Amaryllidaceae, onion and leek lectins, the orchid lectins were also shown to be very potent inhibitors of the infection of target cells by some human and animal retroviruses (Balzarini et al, 1991(Balzarini et al, , 1992. Using double-immunodiffusion assays it was shown that the orchid lectins isolated from L. ovata, E. helleborine and Cymbidium hybrid also react with antibodies raised against the snowdrop lectin and cross react with the G. nivalis lectin, indicating that these Orchidaceae lectins are serologically related to the snowdrop lectin.…”
Section: Discussionmentioning
confidence: 99%
“…Since all orchid lectins strongly resemble each other with respect to their molecular structure and carbohydrate-binding specificity, and also strongly resemble the previously isolated Amaryllidaceae lectins in terms of molecular structure and antiviral properties (Balzarini et al, 1991(Balzarini et al, , 1992, it seemed worthwhile to examine a possible serological relationship between these lectins. Polyclonal antisera prepared against the L. ovata lectin and the G. nivalis lectin were challenged with the different orchid lectins and the snowdrop lectin.…”
Section: Biochemical and Physicochemical Characterization Of The Orchmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). Moreover, the prevalence of Man 5 GlcNAc 2 compared with recombinant envelope may explain the surprising antiviral efficacy of lectins to Manα1→3 and Manα1→6 terminating glycans (39). Furthermore, as the most conserved and abundant glycan structure on the viral envelope, Man 5 GlcNAc 2 should itself be evaluated as a target for vaccine design.…”
Section: Discussionmentioning
confidence: 99%
“…Lectins are also particularly relevant to human immunodeficiency virus (HIV) pathogenesis. Lectin-induced inhibition of syncytium formation and infection of cells by both T-cell line adapted and primary isolates (21)(22)(23)(24)(25)(26)(27) focuses attention on oligomannosidic glycans, such as those characterized by interaction with ConA ( Fig. 1).…”
mentioning
confidence: 99%